Application of Multi-Criteria Decision-Making Methods in Mineral Processing—A Review - Zoran Štirbanović; Dragiša Stanujkić; Jovica Sokolović; Ivana Ilić (Materials Proceedings, 2023)
Multi-criteria decision-making (MCDM) methods represent an efficient mathematical tool for making selections between several alternatives which are seemingly similar and also when a large number of influential criteria need to be taken into consideration. In other words, MCDM methods make difficult choices easier, so that was the reason why they found applications in various areas of life, industry, science, etc. In mineral processing, when conducting scientific research or in industrial practice, it is often necessary to make different kinds of decisions based on several often-conflicting parameters such as technological, economic and environmental parameters. Making the wrong choices can affect the industrial process, result in additional expenses and endanger the health of workers and the environment, thus the application of MCDM methods can be the solution and give additional help in decision-making processes. In the past few decades, a large number of MCDM methods were developed, and some of them have found application in mineral processing for different purposes, such as the selection of various equipment (flotation machines, crushers, etc.), the selection of flotation collectors and other reagents used in mineral processing, and the selection of technologies for processing different raw materials, grinding circuits, and so on. In this paper, a comprehensive overview of the used MCDM methods and their applications regarding mineral preparation and processing will be given.